2023
DOI: 10.1097/wnn.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroanatomy of Poststroke Subjective Sensory Hypersensitivity

Abstract: Background: Although subjective sensory hypersensitivity is prevalent after stroke, it is rarely recognized by health care providers, and its neural mechanisms are largely unknown. Objective: To investigate the neuroanatomy of poststroke subjective sensory hypersensitivity as well as the sensory modalities in which subjective sensory hypersensitivity can occur by conducting both a systematic literature review and a multiple case study of patients with subjective sensory hypersensitivity. Method: For the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…About 18% of patients with brain injury report experiencing sensory hypersensitivity subsequent to their injury ( Chung and Song, 2016 ). As such, a review of studies examining patients with post-stroke subjective sensory hypersensitivity ( Thielen et al, 2023 ) found a link between sensory hypersensitivity and lesions to the insula—a brain region commonly shown in fMRI studies of SPS (e.g., Acevedo et al, 2018 ). Thus, the relationship between SPS and medication sensitivity can serve as an easily measurable marker for sensory hypersensitivity in general.…”
Section: Introductionmentioning
confidence: 99%
“…About 18% of patients with brain injury report experiencing sensory hypersensitivity subsequent to their injury ( Chung and Song, 2016 ). As such, a review of studies examining patients with post-stroke subjective sensory hypersensitivity ( Thielen et al, 2023 ) found a link between sensory hypersensitivity and lesions to the insula—a brain region commonly shown in fMRI studies of SPS (e.g., Acevedo et al, 2018 ). Thus, the relationship between SPS and medication sensitivity can serve as an easily measurable marker for sensory hypersensitivity in general.…”
Section: Introductionmentioning
confidence: 99%